A dynamic interplay between membranes and the cytoskeleton critical for cell development and signaling - Clement Thomas; Christopher J Staiger (Frontiers Media SA, 2014)
Various cellular processes underlying plant development and response to environmental cues rely on a dynamic interplay between membranes and the cytoskeleton, e.g. vesicle and organelle trafficking, endocytosis, exocytosis, and signal transduction. In recent years, significant progress in the understanding of such interplay has been achieved and several critical links between membranes and the cytoskeleton have been characterized. As an example, recent work has clarified how auxin promotes the reorganization of cortical actin filaments by the activation of Rho GTPase pathways, and how such reorganization in turn locally modifies endocytosis and/or exocytosis and directs asymmetric distribution of PIN family of auxin transporters. Another recent achievement is the characterization of the Rho- and microtubule-driven mechanism by which the cell wall architecture is established. In particular, the elegant work by Oda and Fukuda (Science 337 p.1333, 2012) provides evidence that secondary wall patterning in xylem vessel primarily relies on two processes: a local activation of the plant Rho GTPase ROP11 and a mutual, MIDD1-mediated, inhibitory interaction between active ROP domains and cortical microtubules. Additional examples include recent genetic evidence that microtubule and actin filament interacting/regulatory proteins, such as MAP65-1 and capping protein, function as transducers of membrane lipid signaling into changes in cytoskeleton dynamics and organization. This Research Topic aims at collecting a comprehensive set of articles dealing with cellular processes involving membrane-cytoskeleton interactions. Its scope extends beyond the specific fields defined by the above examples and includes intracellular trafficking, host-pathogen interactions, response to biotic and abiotic stresses and hormonal regulation of growth. We hope that this Research Topic will also highlight critical questions that need to be addressed in the future. We welcomed Original Research Articles, Technical/Methodological Advances (e.g. analysis of cytoskeleton dynamics close to membranes), Reviews and Mini Reviews that can expand our understanding of how and why membranes and the cytoskeleton interact.
English
Keywords: Cell Wall; signaling lipids; Actin; Microtubules; Cytoskeleton; Membrane trafficking